Translational Control during Cellular Senescence - Payea, Matthew J.; Anerillas, Carlos; Tharakan, Ravi; Gorospe, Myriam (Molecular and cellular biology, 2021)
Senescence is a state of long-term cell cycle arrest that arises in cells that have incurred sublethal damage. While senescent cells no longer replicate, they remain metabolically active and further develop unique and stable phenotypes that are not present in proliferating cells. On one hand, senescent cells increase in size, maintain an active mTORC1 complex, and produce and secrete a substantial amount of inflammatory proteins as part of the senescence-associated secretory phenotype (SASP). On the other hand, these progrowth phenotypes contrast with the p53-mediated growth arrest typical of senescent cells that is associated with nucleolar stress and an inhibition of rRNA processing and ribosome biogenesis. In sum, translation in senescent cells paradoxically comprises both a global repression of translation triggered by DNA damage and a select increase in the translation of specific proteins, including SASP factors.